Evaluating the simulation times and mass balance errors of component-based models: An application of OpenMI 2.0 to an urban stormwater system. (October 2015) - Buahin, Caleb A.; Horsburgh, Jeffery S.
Abstract: In making the decision whether to use component-based modeling, its benefits must be balanced against computational costs. Studies evaluating these costs using the Open Modeling Interface (OpenMI) have largely used models with simplified formulations, small spatial and temporal domains, or a limited number of components. We evaluate these costs by applying OpenMI to a relatively complex Stormwater Management Model (SWMM) for the City of Logan, Utah, USA. Configurations of coupled OpenMI components resulting from decomposing the stormwater model by process (i.e., runoff coupled to routing) and then by space (i.e., groups of catchments coupled together) were compared to a reference model executed in the standard SWMM configuration. Simulation times increased linearly with the number of connections between components, and mass balance error was a function of the degree to which a component resolved time series data received. This study also examines and proposes some strategies to address these computational costs. Highlights: We compared coupled OpenMI components with equivalent standard SWMM configuration. SWMM was decomposed by process and space to explore coupling performance penalties. Performance was evaluated in terms of simulation time and mass balance error. We illustrate performance penalties to consider when using component-based models. Strategies to address computational costs of component-based models are proposed.